THE INFLUENCE OF THE INSTAGRAM APPLICATION ON THE LIFESTYLE OF GENERATION 5.0 STUDENTS AT TADRIS IPS 2020 UIN KIAI HAJI ACHMAD SIDDIQ JEMBER - Miftahul Laili; Depict Pristine Adi (SOLIDARITY: Journal of Social Studies, 2022)
As technology develops, IPS (Social Studies) students use Instagram a lot to find information. besides that it is used to view videos or photos uploaded by influencers who are active on Instagram. Students who generally have the age of 19 – 20 years who can already imitate the styles that are trending on Instagram are faster to imitate either by dressing or speaking as well as following existing trends. Generation 5.0 students who easily access Instagram can also find the desired student entertainment on Instagram, either in the form of funny things or shopping, which causes students to be consumptive because there are many features on Instagram, and Generation 5.0 students are very easy to access because Instagram is on the cellphone they hold. This scientific work is an illustration of how the influence of Instagram on the lifestyle of the 5.0 generation Social Sciences students. This research is a qualitative method in the form of previous scientific works and interviews with IPS students. This study aims to determine the lifestyle of students when using Instagram. From the various stages above, it can be seen that Instagram has an effect on the lifestyle of Social Science students at UIN Kiai Haji Achmad Siddiq Jember.